Cajal bodies are developmentally regulated during pollen development and pollen tube growth in Arabidopsis thaliana - Scarpin, Maria Regina (2013)
In order to investigate whether the number and size of the CBs vary during the cell divisions and cellular differentiation that occur during pollen development, we used Arabidopsis thaliana pollen. Here, we show that CB cellular distribution varies at different stages of pollen development. Furthermore, the size and number of CBs vary between vegetative and sperm cells of mature and germinated pollen. We suggest that these variations in size and number occur in order to respond to changing gene expression patterns throughout pollen development and germination.